Association between bmi and waist circumferences with eating behavior among undergraduate Students In Universiti Sains Malaysia, Health Campus, Kubang Kerian, Kelantan - Rozak, Nurulnajwa Abdul (Universiti Sains Malaysia, 2024)
Obesity and related health issues are rising concerns among young adults, particularly undergraduate students. Body Mass Index (BMI) and waist circumference are critical indicators of obesity, and eating behavior significantly influences these metrics. Understanding the association between BMI, waist circumference, and eating behavior can inform targeted interventions to promote healthier lifestyles. This study aims to explore the association between BMI, waist circumference, and eating behavior among undergraduate students. A cross-sectional study was conducted involving 179 undergraduate students aged 19 above from Universiti Sains Malaysia Kubang Kerian, Kelantan. Participants in this study were 146 female respondents (81.6%) and 33 male respondents (18.4%). Anthropometric measurements, including BMI and waist circumference, were recorded. Eating behavior was assessed using the Adult Eating Behavior Questionnaire (AEBQ), which evaluates emotional, external, and restrained eating patterns. Statistical analyses, including Spearman’s correlation and multiple regression, were performed to determine the associations between BMI, waist circumference, and eating behaviors. The study found there is a significant positive weak association between BMI with food approach, Emotional Over-Eating (EOE), (r = 0.18, p = 0.02). Meanwhile, Slowness in Eating (SE) showed there is a significant negative weak association between BMI and food avoidance subscales (r = - 0.17, p = 0.02). Next, there is a significantly weak negative correlation waist circumference with Satiety Responsiveness (SR) (r = -0.17, p = 0.03). Emotional Under-Eating (EUE) also showed there is significantly weak negative association between waist circumferences and food avoidance subscale.